From higher education to employment : synthesis report - (:unkn) unknown (My University, 1993)
Four volumes, published in the series of "OECD Dokuments", gather together all of the data available in OECD countries at the end of 1990 on flows of graduates from higher education and their entry into empolyment. This report analyses this information, summarises the issues and endeavours to identify the main challenges for the 1990s. The aim of Part One is to show how the higher education "output" has evolved over the past ten years, to study the nature of the adjustments between training and employment and to see to what extent the institutional framework and higher education policies have favoured evolutions corresponding to labour market needs or employment possibilities. In Part Two the authors describe the situation of young graduates from higher education on the labour market. This is not limited to defining the situation of young graduates relative to young people emerging from other levels of training: an effort is made above all to shed light on disparities in the situations of different categories of graduates, according to the level and nature of their studies. (IAB2) Der Band fasst die Ergebnisse der Berichte über die Entwicklung der Hochschulabsolventen und ihre berufliche Integration in ausgewählten OECD-Ländern zusammen. Teil 1 beschreibt die Entwicklung der Absolventenzahlen in den letzten 10 Jahren und beschäftigt sich mit der Reaktion des Bildungssystems auf die sich wandelnden Qualifikationsanforderungen. Teil 2 analysiert die Situation der Absolventen beim Eintritt in den Arbeitsmarkt. (IAB)
Von der Hochschule auf den Arbeitsmarkt - Zusammenfassender Bericht
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; S 1.4.1 Ausbildung an Fachhochschulen; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 2.3.1 Arbeitsteilung & -organisation; G 1.3.3.4 Wiedereingliederung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 1.4 Hochschulbildung; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 5 Organisationsentwicklung; Hochschule; Fachhochschule; Absolvent; Berufseinmündung; Berufliche Integration; Arbeitsmarktchance; Qualifikationsanforderung; Bildungsbeteiligung; Entwicklung; Studienfachwahl; Geschlechtsspezifische Faktoren; Studienabbruch; Arbeitslosigkeit; Beschäftigtenstruktur; Quantitative Angaben